2016
DOI: 10.1155/2016/5026984
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase: A Potential Target for Treatment of Stroke

Abstract: Stroke is the third leading cause of death in industrialized nations. Oxidative stress is involved in the pathogenesis of stroke, and excessive generation of reactive oxygen species (ROS) by mitochondria is thought to be the main cause of oxidative stress. NADPH oxidase (NOX) enzymes have recently been identified and studied as important producers of ROS in brain tissues after stroke. Several reports have shown that knockout or deletion of NOX exerts a neuroprotective effect in three major experimental stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 89 publications
0
41
0
Order By: Relevance
“…Ischemia-induced deficiency of oxygen and glucose disrupt mitochondrial homeostasis and metabolism in brain neurons, resulting in the conversion of O 2 to O 2 . -(superoxide radical) and other reactive oxygen species (ROS) rather than utilization of O 2 for oxidative phosphorylation and adenosine triphosphate generation (25)(26)(27). Furthermore, blood reperfusion following ischemia leads to the activation of nicotinamide adenine dinucleotide phosphate oxidases, lipoxygenase and xanthine oxidase, all of which may produce ROS (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ischemia-induced deficiency of oxygen and glucose disrupt mitochondrial homeostasis and metabolism in brain neurons, resulting in the conversion of O 2 to O 2 . -(superoxide radical) and other reactive oxygen species (ROS) rather than utilization of O 2 for oxidative phosphorylation and adenosine triphosphate generation (25)(26)(27). Furthermore, blood reperfusion following ischemia leads to the activation of nicotinamide adenine dinucleotide phosphate oxidases, lipoxygenase and xanthine oxidase, all of which may produce ROS (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…-(superoxide radical) and other reactive oxygen species (ROS) rather than utilization of O 2 for oxidative phosphorylation and adenosine triphosphate generation (25)(26)(27). Furthermore, blood reperfusion following ischemia leads to the activation of nicotinamide adenine dinucleotide phosphate oxidases, lipoxygenase and xanthine oxidase, all of which may produce ROS (25)(26)(27). Overproduction of ROS challenges the antioxidative system in neurons and poses oxidative damage to substances, such as lipids, that are rich in neurons but vulnerable to free radicals (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS constitute the most important factor for oxidative stress, and the major source of ROS is NADPH oxidase [54], which has been a potential target for the treatment of stroke [55]. Downregulation of nitrotyrosine protected neurons against ischemia injury [56].…”
Section: The Potential Of Acupuncture For Secondary Prevention Of Strmentioning
confidence: 99%
“…Another important source of ROS production is NADPH oxidase (NOX), a key component of electron transport chain in the plasma membrane, which generates free radicals by transferring one electron to molecular oxygen [13]. Experimental studies demonstrated that NOX2 gene deletion reduces BBB dysfunction and infarct size after filament MCAO for 2 h followed by reperfusion in mice [14], indicating the contribution of NOX in the pathogenesis of ischemia-reperfusion injury, and the potential of targeting NOX as a therapeutic strategy [15]. …”
Section: Pathophysiological Mechanisms Of Cerebral Ischemia-reperfusimentioning
confidence: 99%